Myxomycetes biodiversity in Gaziantep Province (Turkey) with four new records - Baba Hayri̇; Gündoğdu, Fatma; Sevi̇ndi̇k Mustafa (Phytotaxa, 2021)
Myxomycetes were cultured in moist chambers using substrate material collected in Gaziantep province, Turkey, during 2017–2019. Fruit bodies of wild myxomycetes were collected at ten locations. Rotten or live tree bark, leaves, debris, vegetable, and animal material, which were considered likely to contain spores, were also collected. Natural samples were immediately dried, and potential spore-bearing material was kept in a warm and humid environment with the moist chamber technique. A total of 537 samples were studied and 203 myxomycetes isolates were obtained, 33 of which were natural samples, 76 were obtained with the moist chamber technique and 94 were obtained both naturally and with the moist chamber technique in the laboratory. Six orders, 9 families, 16 genera and 42 species were identified in 3 subclasses. All species were new in Gaziantep province and four myxomycetes were identified as new records in Turkey; Didymium atrichum Henney & Alexop., Didymium serpula Fr., Craterium obovatum Peck and Physarum bivalve Pers. were added to the Turkish mycota.